Character Education at Sekolah Alam Minangkabau and Sekolah Alam Ar-Royyan Padang - Indah Pertiwi; Syafri Anwar (International Journal of Educational Dynamics, 2020)
This research discloses how character education builds students’ character at SekolahAlam Minangkabau and SekolahAlamAr-Royyan Padang, so students not only have knowledge capabilities but also provide character social attitudes. This is a qualitative typified research. The data were collected through observation, interviews, and document analysis. The validity of the data was examined through the triangulation method while Miles and Huberman’s theory of analysis were used in analyzing the data. The results of the research suggest that: The characters of the students in both schools are religious, tolerant, obedient, diligent, creative, independent, curious, communicative, ecofriendly, and responsive. The students’ character is built through macro and micro strategies. The varieties of the character education used in both schools include the curriculum, facility, educational program, extracurricular as well as the time and the way the character education is implemented. The students’ parents view the character education as a support for them in developing their children’s personality,itinfluences the students’ daily activities outside the schools,and moreover, it alsoestablishes a good communication between the teacher and the students’ parents.